Pengaruh Penerapan Bundle Know terhadap Pengetahuan dan Kepatuhan Perawat dalam Pencegahan Phlebitis - Eka Puji Hastuti; Chanif Chanif; Edy Soesanto; Vivi Yosafianti Pohan; Rahayu Astuti (Universitas Malahayati, 2026)
ABSTRACT Phlebitis remains a major concern in nursing care as it reflects the quality of hospital services. Low knowledge and compliance of nurses are the main causes of phlebitis, thus efforts to improve nurses’ understanding and compliance in the management of peripheral intravenous catheters are essential. to determine the effect of implementing Bundle Know on nurses’ knowledge and compliance in preventing phlebitis. a quasi-experimental pretest-posttest with control group design was conducted on 99 nurses. The intervention group (n=50) received Bundle Know training (module and workshop) consisting of four components: Keep it Clean, Need for Device, Observe and Secure, Work Together. The control group (n=49) only received standard IM bundle socialization. Instruments included a knowledge questionnaire and a compliance observation checklist. Wilcoxon test showed an increase in the median knowledge score in the intervention group from 24 to 26 (p=0.000), and in the control group from 23 to 24 (p=0.000). Friedman test revealed improved compliance in the intervention group from a median of 9 to 13 (mean rank 1.21 to 4.10;χ²=159.85; p=0.000), and in the control group from 8 to 10 (mean rank 1.82 to 3.93; χ²=79.63; p=0.000). Mann-Whitney tests showed significant differences in posttest knowledge (p=0.001) and compliance (p=0.000) favoring the intervention group. The implementation of Bundle Know effectively improved nurses’ knowledge and compliance in preventing phlebitis. Keywords: Bundle Know, Phlebitis, Knowledge, Compliance Nursing. ABSTRAK phlebitis masih menjadi perhatian utama dalam pelayanan keperawatan karena mencerminkan mutu pelayanan rumah sakit. Rendahnya pengetahuan dan kepatuhan perawat menjadi penyebab utama phlebitis, sehingga upaya peningkatan pemahaman dan kepatuhan perawat dalam manajemen kateter intravena perifer menjadi sangat penting. Mengetahui pengaruh penerapan Bundle Know terhadap pengetahuan dan kepatuhan perawat dalammencegah phlebitis. kuasi-eksperimental pretest-posttest with control group pada 99 perawat. Kelompok intervensi (n=50) mendapat pelatihan Bundle Know (modul dan workshop) dengan 4 komponen: Keep it Clean, Need for Device, Observe and Secure, Work Together. Kelompok kontrol (n=49) hanya menerima sosialisasi bundle IM standar.Instrumen: kuesioner pengetahuan dan lembar observasi kepatuhan. Uji Wilcoxon menunjukkan peningkatan median pengetahuan kelompok intervensi dari 24 ke 26 (p=0,000), kontrol dari 23 ke 24 (p=0,000). Uji Friedman pada kelompok intervensi: kepatuhan meningkat dari median 9 ke 13 (mean rank 1,21 ke 4,10; χ²=159,85; p=0,000). Pada kontrol: meningkat dari 8 ke 10 (mean rank 1,82 ke 3,93; χ²=79,63; p=0,000). Uji Mann-Whitney: pengetahuan intervensi (median=2; IQR=2,25; mean rank=59,29) signifikan lebih tinggi dari kontrol (p=0,001). Kepatuhan juga lebih tinggi (median=30,8 dibandingkan dengan 20,0;p=0,000). Penerapan Bundle Know berpengaruh meningkatkanpengetahuan dan kepatuhan perawat dalam mencegah phlebitis. Kata Kunci: Bundle Know, Phlebitis, Pengetahuan, Kepatuhan Perawat.